ASSESSMENT OF HEALTH AND NUTRITIONAL STATUS UNDER THE INTEGRATED CHILD DEVELOPMENT SERVICES: in The Field Practice Area of Rural Training Health Centre, Nadayara, Travancore Medical College, Kollam-India - Sumit, D.; Abraham,; J. (Udayana University, 2013)
Assessment of health and nutritional status was carried out in Anganwadi Children in the Field Practice Area of Rural Training Health Centre, Nadayara, Travancore Medical College, Kollam. This is a cross sectional study within community base setting. Data were collected by a pretested structured questionnaire and analyzed by applying SPSS. Undernourished children in the Anganwadis under study were 21 %. Growth pattern of these children were significantly associated with the birth weight and the episodes of diarrhea. A significant proportion of children are missing the booster doses. DPT booster (16-24 months) is only 74.1 % and DT booster (5-6 years) is only a meager of 13.6%